EFFICIENT AND SUSTAINABLE ENERGY MANAGEMENT FOR HOSPITAL BUILDING - Sakinah Annura; Jihan Arabikum; Rahmawati Aminingrum; Zainal Ulu; Dwi Wahyudi; Lilik Zuhriyah (Journal of Community Health and Preventive Medicine, 2022)
The development of current environmental problems raises the concerns of investors or hospital lenders about the potential financial problems resulting from current environmental problems. A sustainable health care system can achieve high-quality care and improve public health without wasting resources. The health service sector is continuously encouraged to apply the concept of "Green Hospital" which is one example of the continuity of health services. This research focuses on emission reduction management in health care facilities. This study examines several published papers containing the terms sustainable, green infrastructure, and energy management. Guidelines for Efficient and Sustainable Energy Management in Hospital Buildings is the selected article. The articles used were obtained from the Google Scholar database. Data analysis was carried out descriptively using tables. This study took data from three countries, namely Thailand, Taiwan, and Indonesia, based on our team's observations during a virtual hospital visit to the two countries (Thailand and Taiwan), which we then compared with most hospitals in Indonesia. Currently, there is no Green Hospital standard for each of these countries. The application of the green infrastructure concept can have a positive impact on cost efficiency and hospital sustainability. Energy Saving Opportunities (PHE) is one method that can be used to save energy use in hospitals. The way to do this is to control the use of infrastructure that consumes a lot of energy, such as the use of lights and Air Conditioners (AC), as well as other infrastructure that is not included in vital equipment.